Efforts of South Korean local governments to eexpand the good landlord movement: Focus on property tax reduction and exemption - Imsoo Choi (Global Business & Finance Review (GBFR), 2022)
Purpose: This study aimed to review whether local governments in Korea introduced the Good Landlord Property Tax Reduction and Exemption System (GLPTRES) in a timely and organic manner and promoted the expansion of the Good Landlord Movement by analyzing the system's problems and proposing improvements. Design/methodology/approach: To obtain data about the GLPTRES and tax reduction and exemption outcomes, this study used the Ministry of the Interior and Safety's Information Disclosure System. On January 26, 2022, the researcher requested information disclosure about 15 regional local governments and 187 basic local governments under such regional local governments. Between January 27 and February 25, 2022, the author was notified by all basic local governments of their decisions to disclose information or the non-availability of such information, which was reflected in the analysis. Findings: The timing of property tax reduction and exemption decisions for good landlords was generally late. There was a relationship between regional local governments and their basic local governments in its implementation. Furthermore, the effectiveness of the GLPTRES was found to be generally low. Research limitations/implications: The period of this study was restricted to 2020, and the analysis focused on the 123 local governments that implemented this system. The lessons learned from Korea can be applied to other countries implementing government support for small businesses during crises. Originality/value: This is the first study to analyze the timeliness of resolutions made by local governments on the GLPTRES implemented in Korea for the first time in 2020 to support small business tenants in trouble due to COVID-19, the relationship between local governments, and its effectiveness.
Keywords: 650; COVID-19; Small Business Tenants; Good Landlord Movement; Property Tax Reduction and Exemption; Local Governments